Partial differential equation-based hazy image contrast enhancement. (November 2018) - Nnolim, Uche A.
Abstract: This study describes a modified partial differential equation (PDE)-based algorithm for contrast enhancement of hazy images. The formulation is supported by similarities between haze and low light conditions. The proposed approach employs multi-scale, local-global enhancement of inverted log reflectance and illumination components. These multiple processes are combined in a suitable PDE framework for improved effectiveness. Furthermore, the de-hazing process is automated via gradient-based optimization, eliminating the manual determination of PDE stopping time. Solutions are also devised for visual halo effect, over-enhancement and colour distortion. Based on subjective and quantitative analysis, the proposed technique consistently outperforms several de-hazing algorithms from the literature.